The Impact of Sociocultural Factors on English Language Learning in Language Intensive Programs - Muhammad Irfan Aminulloh; Mohammad Sofyan Adi Pranata (Universitas KH. Abdul Chalim Pacet Mojokerto, 2025)
This study aims to analyze the influence of sociocultural factors on English language learning at the Santri Intensive Development Institution (LIPs) dormitory of SMP Nurul Jadid, under the auspices of Pondok Pesantren Nurul Jadid, Paiton. The examined factors include cultural identity, socioeconomic status, family and community support, peer influence, educational policies, and global media exposure. A qualitative case study approach was employed, involving 50 students, 10 English teachers, and 15 parents as participants. Data were collected through in-depth interviews, participant observation, open-ended questionnaires, and document analysis. The findings reveal that cultural and Islamic values shape students’ attitudes toward English, often creating tension between preserving local identity and learning a foreign language. Socioeconomic status significantly affects students’ access to digital learning resources. Support from families, communities, and peers contributes to learning motivation, while contextualized educational policies enhance the effectiveness of English instruction. Exposure to English-language media positively impacts students’ language skills and attitudes, although the digital divide remains a major barrier.The study recommends the integration of local and Islamic values into English language learning, improved access to media and learning technologies, and the active involvement of families and communities to support a more holistic and culturally relevant educational experience.